SLUM TOURISM: INDONESIAN TOURISM PROMOTION AND DEVELOPMENT STRATEGY (PROBLEM OR SOLUTION) - Wijaya, Verina; Mitasari, Rean; Kusumawijaya, Erris; Adityaji, Rizki; Widyawati, Christy (ITB AAS Indonesia Surakarta, 2024)
Basically, the concept of tourism development and promotion using the Slum Tourism/Poverty Tourism concept is good for projection in tourism development and promotion because tourists directly interact with local communities, increase their sense of human dignity, and offer new ideas to create new ideas. However, this concept has clashes that are not in line with the concept of Indonesian tourism branding, namely